Implementasi Halal Life Style Di Becos Cafe An-Nawawi - Nursobah, Achmad (MADINAH, 2021)
This study is to describe and analyze the application of a halal lifestyle in the food sector by interviewing managers of becos cafes. The results of several studies in the world say that Islam is the largest religion adopted by the average world population. The area that has the largest number of Muslims is the Asia-Pacific region, especially the Indonesian state. Coupled with the development of the halal lifestyle phenomenon around the world, Indonesia has become one of the countries that can develop a halal economic industry while still paying attention to the applied halal lifestyle. The research on the implementation of the halal life style at the Becos café uses descriptive-analytic techniques. The word halal described in the theoretical basis refers to everything that does not deviate from Islamic law. Meanwhile, lifestyle is related to behavior which is composed of activities, interests, and opinions. So the intended lifestyle is all forms of activity that do not deviate from the teachings of Islam. Research conducted at Becos cafe is about how Becos café implements a halal lifestyle as a basis for doing business because the cafe is actually a cottage environment, so researchers are interested in researching and exploring the specifics of the lifestyle in it. The halal lifestyle in the cafe is seen from the halal aspect of its essence, the halal aspect in how to obtain it, the halal aspect in its processing, the halal aspect of consuming, and the halal aspect of using it. As well as some special practices only owned by Becos Café.